Svoboda médií v kolizi s právy třetích osob - Moravec, Ondřej, 1982-; Masarykova univerzita. Katedra ústavního práva a politologie (2006)
Práce se zabývá základními aspekty problematiky kolize svobody projevu ve sdělovacích prostředích a práv třetích osob dotčených sděleními médii. Práce se zabývá především problematikou práva na ochranu osobnosti, a to perspektivou judikatury Evropského soudu pro lidská práva.
The work deals with basic problems of colision of freedom of speech with the rights of third persons in massmedia. The main part of the work pays attention to jurisprudence of European court of human rights in Strasburg. The last part of the work is the summary of conclussion both de lege lata and de lege ferenda using comparative method of interpretation and particularly jurisprudence of European court of human rights.
Rigorózní práce (JUDr.)--Masarykova univerzita, Právnická fakulta, 2006.
Keywords: masmédia; média; svoboda projevu; freedom of speech; mass media; media; rigorózní práce